Customer's Welcoming in the beauty insitute - Michailidou, Nicoletta; Goula, Maria (Health & Research Journal, 2019)
he customer of an aesthetics institute looks for a welcoming and safe place to be taken care of. The establishment of a friendly atmosphere and normal flow of procedures inside the beauty institute as well as providing personalized services play a major role for customers. The personality of the aesthetician and interpersonal relations based on kindness, politeness, stability, humor and dialogue are fundamental virtues for professional success. An organized customer list, recording and keeping personal data of the customer according to current legislation are helpful in solving the customer’s problem properly. The social media, advertising and marketing skills are useful for aestheticians. Strategies that look for innovative and improved ways to meet the clients’ wishes and needs are creative and potent. An aesthetics business has to choose a marketing strategy in order to be competitive. Owners of aesthetics institutes need to put their businesses in the center of special marketing procedures. In addition, adapting to his/her needs according to their sex, age and socioeconomic level is important. Personal hygiene and professional appearance of the aesthetician is equally important.